2012
DOI: 10.3168/jds.2011-4736
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding fresh forage and marine algae on the fatty acid composition and oxidation of milk and butter

Abstract: This study evaluated the effects of feeding fresh forage either as pasture plus a concentrate (PAS) or as a silage-based total mixed ration (TMR), combined with either a ruminally inert lipid supplement high in saturated fatty acids (-) or a ruminally protected microalgae containing 22 g of docosahexaenoic acid (DHA)/100 g of fatty acids (+) on the fatty acid (FA) composition and oxidation of milk and butter. For the 8 mid-lactation Holstein cows in this study, milk yield was not significantly affected by trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
65
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 54 publications
7
65
1
4
Order By: Relevance
“…The positive impact of Spirulina platensis on milk yield was also confirmed by the study conducted by Šimkus et al [52]. Other studies conducted elsewhere however found no effect of feeding algal-based diet on milk yield [53][54][55][56] (Table 3).…”
Section: Peiretti and Meineri [11] Rabbitsupporting
confidence: 77%
See 3 more Smart Citations
“…The positive impact of Spirulina platensis on milk yield was also confirmed by the study conducted by Šimkus et al [52]. Other studies conducted elsewhere however found no effect of feeding algal-based diet on milk yield [53][54][55][56] (Table 3).…”
Section: Peiretti and Meineri [11] Rabbitsupporting
confidence: 77%
“…A study by Panjaitan et al [59] found that supplementing Spirulina platensis to cattle grazing forages with low crude protein can increase the efficiency of microbial protein production in the rumen, which then can be translated into milk products. However, previous studies conducted on lactating cows using marine algal diets found that milk fat [53,56] and milk protein [59,52] were increased while others found a decreased in milk fat [54,55]. The disparities between these studies are mainly due to the different types and sources of marine algae diet used.…”
Section: Milk Protein and Fatmentioning
confidence: 54%
See 2 more Smart Citations
“…Since the concentration of these fatty acids is relatively low for providing health benefits, significant efforts have been devoted to increasing their content in milk and dairy products, in order to produce foodstuffs with improved nutritional value. The main employed strategies are based on the manipulation of the feed and dietary regimen of the animals, and on the modification of the technological processes used in the manufacture of dairy products (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%